REDESIGN WORK STATION CV MASS DIGITAL PRINTING DENPASAR INCREASE PRODUCTIVITY AND REDUCE EMPLOYEE MUSCULOSKELETAL COMPLAINTS - Adrianto, Bagus Arbi; Adiatmika, I Putu Gede; Suardana, I Putu Ery (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2017)
Less ergonomic computer working condition may cause a variety of complaints among computer operators. The complaint arises due to inappropriate of work load and capacity. Less ergonomic working conditions increase muscle tension of several muscles based on surface electromyography, work load, and subjective complaints based on musculoskeletal complaints, fatigue, and eyestrain. The objective of this study was to analyze improvement of the working conditions based on total ergonomic reduce the electrical activity of muscles, work load, musculoskeletal complaints, fatigue, and eyestrain. The true experimental study has been conducted with treatment by subject design among design workers of CV. Massa Denpasar with a total 15 subjects. Some data including muscle tension, work load, musculoskeletal complaints, and fatigue were measured when working in conventional working conditions (first Period) and when working with treated working conditions based on total ergonomic (second Period). Data were analyzed by paired samples t test and Wilcoxon signed ranks test. This study revealed that a decreased of work load was 4,89%, musculoskeletal complaints were 15,45%, fatigue was 33,53%, and eyestrain was 14,32% and productivity was 44,07% (p<0.05). The results showed that the improvement of computer working conditions based on total ergonomic decreased muscle tension, work load, musculoskeletal complaints, fatigue, and eyestrain. Concluded that the improvement of working conditions based computer ergonomics can reduce the total workload is seen from the decrease in pulse work, as well as lowing the musculoskeletal complaints and fatigue are seen from the increase in productivity, suggested that improvements in working conditions is used as a model computer in designing computer working conditions for the achievement of healthy working conditions, safe, convenient, effective, efficient, and productive with the hope that achieved the highest welfare